Ensaios para determinar a (Bio)disponibilidade de chumbo em solos contaminados: revisão Essays for determining lead (Bio)availability in contaminated soils: review - Sergio Tagliaferri Bosso; Jacinta Enzweiler (Química Nova, 2008)
Incidental ingestion of contaminated soils is a major route of Pb uptake by humans, especially by children. Lead speciation in soils controls its bioavailability. Bioavailability assessment requires the determination of the amount of absorbed lead if a contaminated soil is ingested. In vivo tests, which employ animals, are considered the best model to infer absorption of Pb. But they have some logistic limitations and several authors proposed in vitro methods, which simulate conditions of human digestion. Many of them present results which correlate with in vivo essays. Several authors consider in vitro tests a good and reliable alternative to infer lead bioavailability.